Research on the bearing capacity characteristics of initial support for horseshoe‐shaped tunnel prefabrication - Yongtao Xue; Fayuan Yan; Chengzhi Qi; Haochen Zhang; Zhao Xiuwang; Chen Jingxu (Deep Underground Science and Engineering)
Abstract In view of the limited theoretical research on the load model of initial support for horseshoe‐shaped prefabrication, this study focuses on the Luochuan Tunnel on the Xi'an‐Yan'an newly built railway as the research object to explore its load model, load characteristic curve, plastic zone, deformation, and critical thickness. Theoretical research and numerical analysis were conducted. The results indicate that under the same boundary conditions, the ultimate bearing capacity of the prefabricated assembly initial support is higher than that of the shotcrete initial support, resulting in larger ultimate deformation capacity of the prefabricated assembly initial support. Based on numerical calculations, the ultimate deformation and critical thickness of the prefabricated initial lining for single‐ and double‐track railway tunnels are obtained when buried at depths of 200, 500, and 900 m in rock masses of classes III, IV, and V.